Типы проектных рaбот в изучении инострaнных языков - Н. Б. Сaпaрбaевa; М. С. Женисбaевa (Әл-Фараби Атындағы Қазақ Ұлттық Университеті хабаршы шығыстану сериясы, 2018)
This article aims at identifying different types of project work, which is the most essential part of project-based learning. The project-based learning is one of the teaching technologies that affects all components of the education system and the entire teaching and educational process in general. It enables creating a positive environment for education and upbringing, especially for foreign language learning. This method promotes the development of certain intellectual, creative and communicative skills such as, the ability to work with information, generating ideas, problem solving, good communication skills etc.